Effect of antioxidants on primary open-angle glaucoma: a systematic review and meta-analysis - Bao, Jie; Yu, Yujia; Chen, Guosen; Hu, Chen; Zhao, Cong; Li, Xiang (Frontiers in Pharmacology, 2025)
Background/ObjectivesPrimary open-angle glaucoma is a major global cause of vision loss, severely impacting quality of life. Although the need for effective treatments is widely recognized, the efficacy and safety of antioxidants remain uncertain. In this systematic review and meta-analysis, we aimed to evaluate the efficacy and safety of antioxidants in treating patients with primary open-angle glaucoma.MethodsWe reviewed studies from PubMed, Embase, Cochrane Library, and Web of Science published up to 30 November 2024. Eligible studies included adults aged 18–80 years with primary open-angle or normal-tension glaucoma, comparing antioxidant treatment with placebo or comparing a combination of topical treatment and antioxidants with topical treatment alone. Only randomized controlled trials and crossover trials were included. Studies involving secondary glaucoma, ocular inflammation, trauma, or severe systemic disease were excluded, as were nonhuman studies. Of the 518 studies, 15 (2.9%) met the final criteria. Data abstraction and quality assessment followed established guidelines for rigor and transparency. The study outcomes—intraocular pressure, visual field deterioration, ocular blood circulation, blood pressure, and adverse effects—were chosen to evaluate the efficacy and safety of antioxidant treatments in primary open-angle glaucoma.ResultsAnalysis of 15 studies showed that antioxidant supplementation reduces intraocular pressure, improves visual field mean deterioration, and enhances ocular blood circulation in patients with primary open-angle glaucoma. No significant differences were observed in blood pressure or adverse effects between the treatment and placebo groups.ConclusionThis meta-analysis highlights the potential role of antioxidants as a safe and effective therapeutic option for patients with primary open-angle glaucoma.